Transforming Commerce: A Bibliometric Exploration of E-Commerce Trends and Innovations in the Digital Age - Legito, Legito; Eva Andriani (Eastasouth Institute, 2023)
The digital era has ushered in a transformative shift in commerce, culminating in the rise of e-commerce as a dominant force in the global market. This study employs a comprehensive bibliometric analysis, utilizing VOSviewer, to delve into the intricate fabric of e-commerce trends and innovations within the context of the digital age. Through the exploration of publication trends, co-authorship networks, keyword clustering, citation patterns, and emerging technologies, this research maps the intellectual terrain of e-commerce research. The findings illuminate the multidimensional evolution of e-commerce, from personalized mobile experiences to the integration of cutting-edge technologies. The analysis highlights pivotal contributions, collaborative dynamics, and emergent themes, providing a holistic understanding of how commerce has been reshaped in the digital age.